A Duty to Remain Connected: a Biblical Perspective of the Wisdom of the Shabbàt. - Paul Sciberras (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Our labour is intricately woven into our identity, extending beyond mere livelihood. It ought to facilitate personal growth, define our societal roles, and contribute to a common good within the confines of social and environmental sustainability. However, the contemporary work landscape is undergoing profound and global changes, disrupting traditional and conventional notions of work dynamics and its associated relationships. Amidst the diverse and country-specific alterations, a universal paradigm shift is reshaping nearly every sector of the economy. The pressing question emerges: How can we prevent the shift toward more flexible employment from translating into a life of perpetual instability? As job structures become more malleable and the boundaries between professional and personal life blur, the risks of self-exploitation and work-induced stress loom. In navigating these transformations, we must discern the evolving paradigms of work and consider their social and economic repercussions. What lessons are we being prompted to internalize as the European work landscape undergoes unprecedented changes? It becomes imperative to explore these shifts and their implications for a sustainable and equitable future. Exploring the existential insights of the Shabbàt and extracting valuable lessons from biblical wisdom prompts us to ponder the significance of rest in fostering healthy relationships and connectivity—with ourselves, others, our work, and our shared environment. The prevalent culture of constant availability and the obligation to stay connected could benefit from a biblical perspective, particularly in grasping the essence of Shabbàts wisdom.